Impact of nurses' roles and burden on burnout during the COVID‐19 pandemic: Multicentre cross‐sectional survey. (23rd May 2022) - Kishi, Hiromi; Watanabe, Kaname; Nakamura, Sho; Taguchi, Hisako; Narimatsu, Hiroto
Abstract: Aim: To identify groups of nurses engaging in coronavirus disease (COVID‐19) care who are most in need of organizational support. Background: Overwhelming stress and susceptibility to burnout have been reported in nurses during the COVID‐19 pandemic. Methods: Nurses working at five hospitals that accepted COVID‐19 patients answered the questionnaire. The Tokyo Metropolitan Distress Scale for Pandemic, Self‐Diagnosis Check List for Assessment of Workers' Accumulated Fatigue and Japanese Burnout Scale were evaluated. Multiple regression analysis was performed to examine the relationship between engaging in COVID‐19 care and psychosocial/physical burden. Results: In total, 895 questionnaires were analysed. With experience in caring for COVID‐19 patients as the independent variable, nurses caring for suspected cases had significantly higher standardized Tokyo Metropolitan Distress Scale for Pandemic scores for 'concerns for infection' (standardized partial regression coefficient β = .921, P = .004), Assessment of Workers' Accumulated Fatigue (β = .445, P = .022) and Japanese Burnout Scale 'emotional exhaustion' (β = .136, P = .021) than those caring for confirmed cases. Conclusions: Nurses caring for suspected COVID‐19 patients have the highest psychological/physical burden and propensity for burnout. Implications for Nursing Management: Extensive support systems are required for nurses caring for confirmed and suspected COVID‐19 cases.